Upside down book of nuclear power with musings on energy - Jha, Saurav (New Delhi, 2010)
A guide to understanding issues related to nuclear power as energy source Arcane discussions on nuclear power have been confounding people for a long time. The Upside Down Book of Nuclear Power is an attempt to demystify this critical area of public choice for the general reader. While it does not forego the seriousness associated with the topic, the book provides for an easy read that informs the reader of a variety of issues associated with the subject. Divided into short chapters, aspects such as technology, resource availability, economics, geopolitics and policies associated with nuclear power are dealt with in detail, but in a way that emphasizes readability. Contentious areas such as safety, waste management and the latest trends associated with them are laid bare for the reader. The book also dwells in depth on the shrill and seldom above-board debate on nuclear power and renewables. An invaluable companion for all those looking to understand the nature of the nuclear industry in the new millennium and the implications of international treaties such as the Indo-US nuclear deal.
Keywords: Nuclear energy-International co-Operation